Gestión de procesos catastrales a través de paneles de seguimiento del Gad Municipal del cantón Babahoyo - García Burbano, Stephanye Denisse (2020)
The citizens are not satisfied due to the days and weeks that the cadastral process resolution takes within the Municipal GAD of the Canton Babahoyo - Los Ríos-Ecuador, approximately 78.6% of the citizens are dissatisfied due to this inconvenience, this case This study deals with the management of cadastral processes through monitoring panels within this institution, which will reduce response time by automating processes. The methodology of this case study covers: I. Collection of data through the survey and interview. II. Tabulation to obtain a clearer view of the status of cadastral processes. III. Identify the level of feasibility for the implementation of a computerized system for Cadastre processes management through monitoring panels of the Municipal GAD of the Babahoyo canton. Through the results obtained from the survey carried out on 100 citizens, it was determined that 93.9%, as well as the Director of Cadastre of the Municipal GAD of the Babahoyo canton, agrees with the implementation of a computer system that manages the cadastral processes through monitoring panels.